Eisenia bicyclis-Mediated Gold Nanoparticles Exhibit Antibiofilm and Antivirulence Activities Against Pseudomonas aeruginosa and Staphylococcus aureus - Do Kyung Oh; Du-Min Jo; Nam-Gyun Kim; Kyung-Jin Cho; Geum-Jae Jeong; Nazia Tabassum; Won-Kyo Jung; Fazlurrahman Khan; Young-Mog Kim (Antibiotics)
Background/Objectives: Brown algae, particularly Eisenia bicyclis, produce various bioactive chemicals with significant application potential in the food, cosmetics, and pharmaceutical industries. This study aimed to evaluate the antibacterial, antibiofilm, and antivirulence properties of the ethyl acetate fraction (EA) of E. bicyclis and its synthesized gold nanoparticles (EA-AuNPs), with a focus on their potential applications against both Gram-positive and Gram-negative bacteria. Methods: The bioactive component in the ethyl acetate fraction was identified using a gas chromatography-mass spectroscopy (GC-MS) device and a liquid chromatography-mass spectrometer/mass spectrometry (LC-MS) system. The crystal violet method was utilized to evaluate the biofilm inhibition experiments. Several instruments, including dynamic light scattering, Fourier transform infrared, X-ray diffraction, field emission transmission electron microscopy, and energy-dispersive spectroscopy, were employed to completely characterize the produced EA-AuNPs. The cytotoxicity of the EA-AuNPs was determined using the MTT assay, and the expression of genes linked with biofilm and virulence in Pseudomonas aeruginosa and Staphylococcus aureus was investigated using real-time polymerase chain reaction (RT-PCR). Results: Various bioactive compounds were identified from the EA using GC-MS and LC-MS, including fatty acids and phlorotannins such as eckol, dieckol, 6,6’-bieckol, and phlorofucofuroeckol in high amounts, highlighting EA as a phlorotannin-rich fraction. The EA also demonstrated significant antibiofilm activity, with 79.86% inhibition at 512 μg/mL against P. aeruginosa and 87.00% at 64 μg/mL against S. aureus. EA was then used in the synthesis of gold nanoparticles (AuNPs) to improve their stability and safety. The synthesized EA-AuNPs were determined to have an average size of 165.04 nm, with a zeta potential of −29.86 mV, indicating good stability. In antibiofilm activity assays, EA-AuNPs demonstrated 45.76% inhibition against P. aeruginosa at 1024 μg/mL and 44.64% inhibition against S. aureus at 128 μg/mL. At sub-MIC levels, EA-AuNPs significantly inhibited biofilm formation and virulence factors, including the motility of P. aeruginosa and staphyloxanthin synthesis in S. aureus. The RT-PCR analysis revealed the downregulation of key genes involved in biofilm formation and virulence in P. aeruginosa and S. aureus. Conclusions: These findings highlight the potential of E. bicyclis solvent-soluble extracts and EA-AuNPs as effective antibacterial, antibiofilm, and antivirulence agents, with significant application potential in the pharmaceutical and food industries. To the best of our knowledge, this is the first report of antibiofilm activity against both Gram-positive and Gram-negative bacteria using EA-AuNPs.